Effect of Rest Period and Temperature on the Estimation of Fatigue Life of Bituminous Mixture - Pugazhenthi Ayyar; Sundaram Lakshmi; Ajithkumar Padmarekha (The Baltic Journal of Road and Bridge Engineering)
This paper reports the experimental investigation conducted to study the influence of temperature and rest period on different methods of estimation of fatigue life of the bituminous mixture. Four-point beam bending tests were conducted on the bituminous mixture prepared with one unmodified binder and two different modified binders (crumb rubber modified and elastomer modified binder). The test was conducted at 20 °C and 0 °C using continuous loading and a rest period between two load cycles. The fatigue life was estimated using stiffness modulus and energy dissipation. The performance of three different bituminous mixtures was ranked—ranking a bituminous mixture based on the fatigue performance varied with temperature and loading condition. In addition, the ranking also varied with different post-processing methods adopted.